Semantic Changes in Information Communication Terms - Adiba Turahojaeva Khalilullaevna; Abdusattorova Farangiz (Universitas Muhammadiyah Sidoarjo, 2022)
This article deals with linguistic changes in terms of ICT and their initial classroom teaching.